The Role of Visuospatial Representation to Improve Student’s Conceptual Mastery based on Gender in Learning Human Urinary System - A Atikah; Yayan Sanjaya; Nuryani Rustaman (Journal of Science Learning, 2018)
Study of this research investigates the role of visuospatial representation using Wimba model to improve student’s conceptual mastery based on gender in learning Human Urinary System. The method used in this research was experimental research with matching pretest-posttest comparison group design. The sample was taken based on gender classes consisting of boys class (n=21) and girls class (n=9) in one of Bilingual School in Bandung. The quantitative data of this research was investigated through the objective test, while the supportive qualitative data gathered through Likert-Scale. The conceptual mastery of both classes measured based on Bloom’s taxonomy cognitive domain through an objective test. Data processing was done by independent sample t-test. The result of this research shows that there are significant differences in conceptual mastery improvement between girl class and boy class by using visuospatial representation as a model. The research indicates that girl class is outperformed in conceptual mastery almost in each cognitive domain than boy class, and girl class also shows more positive responses toward learning using visuospatial representation than boy class.